2004
DOI: 10.1097/00002820-200411000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Interventions for Patients With Head and Neck Cancer

Abstract: A diagnosis of head and neck cancer, like any cancer diagnosis, is often accompanied by much fear and uncertainty. In addition, patients with head and neck cancer face difficulties in eating, chewing, drinking, breathing, speaking, as well as changes in appearance. Simultaneously, the burden of head and neck cancer is often manifested in psychosocial dysfunction, which can have a negative impact on quality of life. Although a phenomenon well recognized, little is known about many factors that influence or impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 55 publications
3
53
0
5
Order By: Relevance
“…HNC survivors are often from socially disadvantaged backgrounds [2]. Moreover, in the HNC population, lower socioeconomic status and poorer levels of education often go hand-in-hand [2,27]. A recent trial examining productivity and work ability in cancer survivors identified HNC as a cancer that resulted in large reductions in employment and earnings [28].…”
Section: Discussionmentioning
confidence: 99%
“…HNC survivors are often from socially disadvantaged backgrounds [2]. Moreover, in the HNC population, lower socioeconomic status and poorer levels of education often go hand-in-hand [2,27]. A recent trial examining productivity and work ability in cancer survivors identified HNC as a cancer that resulted in large reductions in employment and earnings [28].…”
Section: Discussionmentioning
confidence: 99%
“…Further RCTs were sought via review reference lists [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The systematic review was limited to results from English-speaking samples to minimise problems in generalising results across languages and cultures.…”
Section: Systematic Review Strategymentioning
confidence: 99%
“…Patients often suffer from different sequelae from the cancer itself, side effects of treatment, and individual factors such as unhealthy eating habits and alcohol and tobacco abuse [7]. Frequent sequelae are trismus, swallowing problems, dry mouth, shoulder disability, lymphedema, speech impediments, altered physical appearance, and psychological distress [8][9][10]. The process of returning to work is problematic in some HNC survivors but not all.…”
Section: Introductionmentioning
confidence: 99%